Hyperoxia and hypertonic saline in patients with septic shock (HYPERS2S): a two-by-two factorial, multicentre, randomised, clinical trial. Issue 3 (March 2017) - Asfar, Pierre; Schortgen, Frédérique; Boisramé-Helms, Julie; Charpentier, Julien; Guérot, Emmanuel; Megarbane, Bruno; Grimaldi, David; Grelon, Fabien; Anguel, Nadia; Lasocki, Sigismond; Henry-Lagarrigue, Matthieu; Gonzalez, Frédéric; et al.
Summary: Background: There is insufficient research into the use of mechanical ventilation with increased inspiratory oxygen concentration (FiO2 ) and fluid resuscitation with hypertonic saline solution in patients with septic shock. We tested whether these interventions are associated with reduced mortality. Methods: This two-by-two factorial, multicentre, randomised, clinical trial (HYPERS2S) recruited patients aged 18 years and older with septic shock who were on mechanical ventilation from 22 centres in France. Patients were randomly assigned 1:1:1:1 to four groups by a computer generated randomisation list stratified by site and presence or absence of acute respiratory distress syndrome by use of permuted blocks of random sizes. Patients received, in an open-labelled manner, mechanical ventilation either with FiO2 at 1·0 (hyperoxia) or FiO2 set to target an arterial haemoglobin oxygen saturation of 88–95% (normoxia) during the first 24 h; patients also received, in a double-blind manner, either 280 mL boluses of 3·0% (hypertonic) saline or 0·9% (isotonic) saline for fluid resuscitation during the first 72 h. The primary endpoint was mortality at day 28 after randomisation in the intention-to-treat population. This study was registered withClinicalTrials.gov, numberNCT01722422 . Findings: Between Nov 3, 2012, and June 13, 2014, 442 patients were recruited and assigned to a treatment group (normoxia [n=223] or hyperoxia [n=219]; isotonic [n=224] or hypertonic [n=218]). The trial was stopped prematurely for safety reasons. 28 day mortality was recorded for 434 patients; 93 (43%) of 217 patients had died in the hyperoxia group versus 77 (35%) of 217 patients in the normoxia group (hazard ratio [HR] 1·27, 95% CI 0·94–1·72; p=0·12). 89 (42%) of 214 patients had died in the hypertonic group versus 81 (37%) of 220 patients in the isotonic group (HR 1·19, 0·88–1·61; p=0·25). We found a significant difference in the overall incidence of serious adverse events between the hyperoxia (185 [85%]) and normoxia groups (165 [76%]; p=0·02), with a clinically relevant doubling in the hyperoxia group of the number of patients with intensive care unit-acquired weakness (24 [11%] vs 13 [6%]; p=0·06) and atelectasis (26 [12%] vs 13 [6%]; p=0·04) compared with the normoxia group. We found no statistical difference for serious adverse events between the two saline groups (p=0·23). Interpretation: In patients with septic shock, setting FiO2 to 1·0 to induce arterial hyperoxia might increase the risk of mortality. Hypertonic (3%) saline did not improve survival. Funding: The French Ministry of Health.